Kesalahan Fonologis dan Hubungannya dengan Al-Qur'an: Studi Analitis - Uwoh Abdullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze phonological errors in reading the Qur'an and understand the relationship between these errors and certain aspects of tajwid learning and teaching. Using an analytical study approach, this research evaluates various phonological errors that occur among readers of the Qur'an, with a focus on how these errors affect the quality of reading and understanding of the holy text. The methods used include qualitative analysis of recorded data on Al-Qur'an readings, interviews with tajwid teachers, as well as a review of related literature. The results of the analysis show that the most common phonological errors include errors in letter pronunciation and recitation, as well as inaccuracies in intonation and vowel length. This research also identified that these errors are often influenced by factors such as a lack of understanding of the rules of recitation, the influence of the mother tongue, and a lack of structured practice. These findings suggest the need for a more systematic and adaptive teaching approach to overcome phonological errors, as well as improved evaluation methods to support the development of readers' ability to understand and pronounce the Qur'an correctly.